Assembly of a CdS quantum dot–TiO2 nanobelt heterostructure for photocatalytic application: towards an efficient visible light photocatalyst via facile surface charge tuning. (28th October 2014) - Zhang, Junyu; Xiao, Fang-Xing; Xiao, Guangcan; Liu, Bin
Abstract : CdS QD sensitized TiO2 nanobelt nanostructures were fabricated by a facile self-assembly approach and the photocatalytic performance of the well-defined hybrid heterostructure was systematically probed. Abstract : In recent years increasing efforts have been devoted to synthesizing hybrid semiconductor nanocomposites; however, it still poses a challenge to fabricate well-defined semiconductor based heterostructures. In this work, a well-defined TiO2 nanobelt functionalized with a CdS quantum dot ( viz. TiO2 NB–CdS QD) binary nanostructure has been fabricated by an efficient self-assembly approach based on a facile surface charge tuning. A collection of techniques including X-ray diffraction (XRD), UV-vis diffuse reflectance spectra (DRS), field emission scanning electron microscopy (FESEM), transmission scanning electron microscopy (TEM), and X-ray photoelectron spectra (XPS) was utilized to characterize the structure of TiO2 NB–CdS QD binary heterostructure. It was found that the as-constructed TiO2 NB–CdS QD heterostructure exhibits significantly enhanced photocatalytic performance for the degradation of organic pollutants under visible light irradiation in comparison with blank TiO2 NBs and randomly mixed counterparts. The significantly enhanced photocatalytic performance of the TiO2 NB–CdS QD heterostructure can be attributed to the synergistic contribution from the enhanced light absorption intensity of the hybrid nanocomposite and intimate interfacial contact between CdS QD and TiO2 NB ingredients afforded by the electrostatic self-assembly buildup, which remarkably facilitates charge separation and lengthens the lifetime of photogenerated electron–hole pairs under visible light irradiation. Moreover, it was demonstrated that the TiO2 NB–CdS QD heterostructure shows favorable photostability on account of intrinsic protection by a surface ligand of CdS QDs. In addition, the possible photocatalytic mechanism was tentatively proposed and predominant active species during the photocatalytic process were unambiguously determined.